2020
DOI: 10.3389/feduc.2020.584351
|View full text |Cite
|
Sign up to set email alerts
|

Factors and Recommendations to Support Students’ Enjoyment of Online Learning With Fun: A Mixed Method Study During COVID-19

Abstract: Understanding components that influence students’ enjoyment of distance higher education is increasingly important to enhance academic performance and retention. Although there is a growing body of research about students’ engagement with online learning, a research gap exists concerning whether fun affect students’ enjoyment. A contributing factor to this situation is that the meaning of fun in learning is unclear, and its possible role is controversial. This research is original in examining students’ views … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 46 publications
0
17
0
2
Order By: Relevance
“…According to the findings of a study, 88.77 percent of participants believed that enjoyment in online learning was associated with well, motivation, and competence. However, 16.66 percent of respondents said that the pleasure of online learning might divert their attention away from their academics, resulting in distraction or time loss (Okada & Sheehy, 2020) Based on the findings, it can be said that students are well motivated when they learn from home. The online learning system provides customized content for children based on their own experience and ability level, ultimately helping learners improve their learning motivation (Duffy & Azevedo, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…According to the findings of a study, 88.77 percent of participants believed that enjoyment in online learning was associated with well, motivation, and competence. However, 16.66 percent of respondents said that the pleasure of online learning might divert their attention away from their academics, resulting in distraction or time loss (Okada & Sheehy, 2020) Based on the findings, it can be said that students are well motivated when they learn from home. The online learning system provides customized content for children based on their own experience and ability level, ultimately helping learners improve their learning motivation (Duffy & Azevedo, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…At present, scholars have conducted research on related content. Okada and Sheehy (2020) used a hybrid method to investigate the beliefs and attitudes of 551 distance education students, and the results showed that 88.77% of participants value the fun of online learning related to happiness, motivation and performance; 16.66% of people thought that the fun of online learning would distract them, cause distraction or waste time, etc. Bhagat et al .…”
Section: Literature Reviewmentioning
confidence: 99%
“…As the pandemic keeps coming back with different variants such as Delta and Omicron, it is still necessary under various circumstances for teachers worldwide, including those in China, to teach online. What is more important, as blended learning is becoming increasingly important in an extensive range of disciplines ( Holbeck and Hartman, 2018 ; Gonzalez and Knecht, 2020 ; Veerapen et al, 2020 ), it is necessary to switch our attention not only to learners ( Holbeck and Hartman, 2018 ; Gillis and Krull, 2020 ; Okada and Sheehy, 2020 ; Kohnke et al, 2021 ; Maheshwari, 2021 ; Wang and Jiang, 2022 ), but further to teachers, whose degree of enjoyment during online teaching has an impact on both their own well-being ( Anderson et al, 2021 ; Creely et al, 2021 ; Mahmood et al, 2021 ), and the emotion, well-being and learning enjoyment of students ( Badia et al, 2019 ; Eloff et al, 2021 ; Ergun and Dewaele, 2021 ; Goenner, 2021 ; Meishar-Tal and Levenberg, 2021 ; Naylor and Nyanjom, 2021 ).…”
Section: Introductionmentioning
confidence: 99%